Urbanización y transporte. Algunos aportes conceptuales - Kralich, Susana (2016)
The literature regarding the study of big cities and in particular the analysis of its expansion, refers to the use of concepts such as metropolis, agglomeration, big city, zone - area - metropolitan region, conurbation, megalopolis, urban region, and more recently, metapolis, in a more comprehensive way than the notion of city . However, these expressions are often used without consensus or certainties about their precise meaning, territorial scope and structural condition. In addition, and regardless of the degree of agglomeration inside the conurbation, the importance of identifying the functional city with some degree of accuracy concerns administrative and management reasons. Indeed, a minimum coordination is needed due to the plurality of districts involved, upon which there are flow developments, service networks and problem generations, whose resolution necessarily has to be agreed by the governments involved, as well as by other social actors. In this article we offer some conceptual clarification on these issues, trying to support their most appropriate use as terms to define processes and complex configurations. We also add a methodological proposal which, applied to the case study, is deemed useful for the determination of the respective territorial scopes.